Securing new space: on satellite cyber-security - Pavur, J (2021)
Satellites offer critical services impacting the lives of billions around the world. However, the cyber-security properties of space systems are poorly understood. As the next generation of space missions begins to launch, there exists an acute need for robust and open research on space systems security.